Pengaruh penempatan, pengalaman dan motivasi kerja terhadap kinerja karyawan PT.Unity Nickel Alloy indonesia Dikabupaten Bantaeng - Oktavia, Nursanti Dwi; Ramly, Mansyur; Sukmawati, St. (Innovative: Journal Of Social Science Research, 2025)
This study aims to examine the current employee performance at PT. Unity Nickel Alloy Indonesia in Bantaeng Regency. The variables used in this research include Placement (X1), Experience (X2), Work Motivation (X3), and Employee Performance (Y). The sample for this study consists of 75 respondents. This study employs a quantitative research design using primary data. The sampling technique used is purposive sampling. The analysis methods applied in this research include data validity testing, reliability testing, normality testing, multicollinearity testing, heteroscedasticity testing, multiple linear regression analysis, simultaneous effect testing (F test), partial effect testing (t test), and simultaneous determination test (R2). The results of the study show that: (1) Placement has a positive and significant effect on employee performance at PT. Unity Nickel Alloy Indonesia in Bantaeng Regency; (2) Experience has a positive and significant effect on employee performance at PT. Unity Nickel Alloy Indonesia in Bantaeng Regency; (3) Work Motivation has a positive and significant effect on employee performance at PT. Unity Nickel Alloy Indonesia in Bantaeng Regency.